Penerapan Model CTL Untuk Meningkatkan Hasil Belajar Pada Sumber Daya Alam Siswa Kelas IV UPT SDN 81 Pinrang - Hasnah Hasnah; Fajar Fajar; Restu Restu (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
This study examines the application of the CTL model to improve student learning outcomes in SDA Class IV UPT SDN 81 Mattiro Bulu Materials, Pinrang Regency. The approach used is a qualitative approach. The type of research is classroom action research (CAR). The focus of this research is the focus of the process and student learning outcomes on natural resource materials by applying the CTL model. Data collection techniques used are observation, tests, and documentation. The subjects of this study were teachers and students consisting of 25 students. The implementation of this classroom action research is planned to consist of four components, namely: 1) Planning, 2) Action, 3) Observation and 4) Reflection. This research was conducted in two cycles. The results of the research in the first cycle were in the Less category and there was an increase in the second cycle, namely the presentation of learning outcomes in the good category and had reached the predetermined indicators. The conclusion in this study is that applying the CTL model can improve the learning process and learning outcomes in natural resource materials for Class IV students of UPT SDN 81 Pinrang.